Diagnosis-related groups and payments for the treatment of malignant neoplasms in the model of 2019 - D. V. Fedyaev; V. V. Omelyanovskiy; M. L. Lazareva; Yu. V. Seryapina; Yu. A. Ledovskikh (IRBIS LLC, 2019)
The article addresses the model of diagnosis-related groups (DRG) updated according to the new tariffs in the compulsory medical insurance. Especially emphasized are changes made in the DRG model of 2019, which resulted from the previous work on the development and revision of the clinical recommendations in oncology, as well as the regulation changes in the healthcare system. In addition, the article describes the functioning of the DRG model in 2018 and the payment for cancer care and also provides examples from the practice of chemotherapy. The modifications made in the 2019 model are carefully discussed in terms of: expanding the list of oncological diagnoses, creating and characterizing new DRG groups, updating the coding system and the structure of reference books, changing the Guidebook recommendations and the Instruction related to oncological groups. Clarifications are given regarding frequently asked questions on payments for the medical care in oncology within the current DRG model.